The Gateway to Computer Science Excellence
+1 vote
357 views

Consider the function $h$ defined on $\{0,1,…….10\}$ with $h(0)=0, \:  h(10)=10 $ and

$$2[h(i)-h(i-1)] = h(i+1) – h(i)  \:   \text{ for } i = 1,2, \dots  ,9.$$

Then the value of $h(1)$ is

  1. $\frac{1}{2^9-1}\\$
  2. $\frac{10}{2^9+1}\\$
  3. $\frac{10}{2^{10}-1}\\$
  4. $\frac{1}{2^{10}+1}$
in Calculus by Loyal (7.1k points)
edited by | 357 views

1 Answer

+3 votes
If we see the sequence carefully , all it is saying is that common difference of the sequence is in Geometric progression with common ratio $2$ .

 $h(0) = 0$ (given)

Let $h(1) = x$

$h(2) = x + 2x = 3x$

$h(3) = 3x + 4x = 7x$

and so on. The general term of the sequence is

$h(n) = (2^n -1) x$ where $x = h(1)$

so $h(n) = (2^n -1) h(1)$ and
$h(10) = 10$ . Substituting we get $C$ as the answer.
by Active (2k points)

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,666 questions
56,131 answers
193,669 comments
93,306 users